Human infection by Angiostrongylus costaricensis in Venezuela: first report of a confirmed case Infección humana por Angiostrongylus costaricensis en Venezuela: primer reporte de un caso confirmado - Renzo Nino Incani; Eduardo Caleiras; Milena Martín; Carlos González (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
A proven case of human infection caused by Angiostrongylus costaricensis is reported for the first time in Venezuela. The patient was a 57-year-old female surgically operated because of signs of peritonitis with a palpable mass at the lower right quadrant of the abdomen. WBC count reported 16,600 cells/mm³, with 46% eosinophils. The tumoral aspect of ileocolic area and peritoneal lymph nodes prompted the resection of a large area of the terminal ileum, cecum, part of the ascending colon and a small part of the jejunum, where a small lesion was found. The pathology showed thickened areas of the intestinal wall with areas of hemorrhage and a perforation of the cecum. Histology showed intense eosinophil infiltration of the whole intestinal wall, granulomas with giant cells and eosinophils. Some of the granuloma surrounded round or oval eggs with content characterized by a large empty area, cells or embryo in the center, and sometimes nematode larvae. A cross section of an adult nematode worm was observed inside a branch of mesenteric artery. The intestinal affected area, the characteristics of the lesions, the presence of eggs in the submucosa with nematode larvae inside, and the observation of a nematode inside a mesenteric artery, makes sufficient criteria for the diagnosis of an infection by Angiostrongylus costaricensis. Un caso comprobado de infección humana por Angiostrongylus costaricensis es reportado para la literatura por vez primera en Venezuela. El paciente fue una mujer de 57 años de edad intervenida quirúrgicamente debido a signos de peritonitis, con una masa palpable en la fosa ilíaca derecha del abdomen. El recuento de leucocitos reportó 16.600 células/mm³ con 46% eosinófilos. El aspecto tumoral del área íleocólica y las adenopatías peritoneales encontradas motivó la resección de un área grande del ileon terminal, ciego, parte del colon ascendente y una pequeña parte del yeyuno donde se encontró una pequeña lesión interpretada como metastásica. La patología mostró áreas engrosadas de la pared ...